Final confession : the unsolved crimes of Phil Cresta - Wallace, Brian P., 1949-; Crowley, Bill (University Press of New England, 2013)
Just before he died in Chicago, legendary thief Cresta revealed to Crowley, a retired Boston police detective, how he planned and carried out the capers that had baffled both the police and his colleagues for decades.